Agrarian reforms, land markets, and rural poor - National Workshop on "Land Markets and Rural Poverty" (2004 : Mussoorie, India); Narasimha Reddy, D.; Centre for Rural Studies (Lal Bahadur Shastry National Academy of Ad ministration) (New Delhi : Published for Centre for Rural Studies, Lal Bahadur S hastri National Academy of Administration, Mussoorie by Concept Pub. Co ., 2009)
Contributed articles largely presented at the National Workshop on " Land Markets and Rural Poverty", held during 10-11 August 2004, at Mus soorie; organised by Centre for Rural Studies, Lal Bahadur Shastry Nati onal Academy of Administration; includes papers from national workshop on whither tenancy, held during Sept. 24-25, 1999.
Includes bibliographical references and index.
Keywords: Land reform -- India -- Congresses; Land tenure -- India -- Congresses; Farm tenancy -- India -- Congresses; Land use, Rural -- Government policy -- India -- Congresses; Rural development -- India